Upper gastrointestinal adverse events and cyclical etidronate. - van Staa, T; Abenhaim, L; Cooper, C (1997)
PURPOSE: Recently, there have been several published case reports of esophagitis associated with the use of aminobisphosphonates. The objective of this study was to evaluate the upper gastrointestinal (GI) safety of cyclical etidronate, an alkylbisphosphonate, in routine clinical practice. PATIENTS AND METHODS: Information was obtained from 550 general practices in the United Kingdom that provide the medical records to the General Practice Research Database. A group of 7977 cyclical etidronate takers and 2 age-, gender-, and practice-matched control groups (1 with osteoporosis and 1 without) were analyzed. RESULTS: For cyclical etidronate takers, the average age was 71.6 years and total follow-up was 10,328 person-years. The risk of upper GI events (inflammation or ulcer of esophagus, stomach, or duodenum) was comparable between patients taking etidronate and the two control groups. The adjusted relative risk of upper GI events was 0.92 (95% confidence interval [CI] 0.78 to 1.09) for etidronate takers compared with osteoporosis controls and 1.12 (CI 0.91 to 1.37) compared to nonosteoporosis controls. For esophagitis and esophageal ulcers, the relative risks were 0.83 (CI 0.64 to 1.08) and 0.97 (CI 0.71 to 1.31) respectively. The incidence of upper GI events during nonsteroidal anti-inflammatory drug (NSAID), aspirin, or corticosteroid use was similar across the three groups. The upper GI risks of etidronate NSAID users were 0.71 (CI 0.45 to 1.11) and 2.06 (CI 0.98 to 4.35) compared with NSAID users in the two control groups. CONCLUSIONS: These results support the GI tolerability and safety profile of cyclical etidronate in routine clinical practice. Concomitant use of cyclical etidronate with NSAIDs, aspirin, or corticosteroids did not increase the incidence of upper GI events.